Software para la inclusión educativa como apoyo al proceso de aprendizaje en los niños con debilidad visual - González Torres, Juan de Dios; Cetz Canche, Nelson Javier; Evilia Magaña, María (Perspectivas Docentes, 2014)
Technology has changed significantly, providing opportunities and possibilities of growing in the field of education and an example of this is the educational software as an important tool in the teaching learning process. However, many schools still lack of this kind of technology. This research comes from a project developed at the university to facilitate the learning in children with different abilities and at the same time to deal with the needs of the Multiple Attention Center (CAM) number 17, located in Paraiso, Tabasco, México.